Model Pembelajaran Problem Solving Dalam Mempengaruhi Kemampuan Pemecahan Masalah Matematika Dengan Pendekatan Polya Pada Materi KPK dan FPB - Fitriyani, Dessy; Arifin, Fatkhul (Media Pendidikan Matematika, 2025)
The low ability of students to solve mathematical problems in the context of learning at school is a challenge, especially in understanding story problems and basic concepts of KPK and FPB through the Polya approach. The learning process that can increase student involvement such as the problem solving learning model. This study aims to evaluate the impact of implementing the problem solving learning model on students' mathematical problem solving abilities. The method used in this study is a quantitative approach with a quasi-experimental design. Data collection techniques are carried out through observation, testing, and documentation. The sample used in the study involved 50 students of class V MIS Jam'iyyatul Khair. Data analysis was carried out using descriptive and inferential methods. The results showed that the average score of mathematical problem solving abilities in the experimental class that applied the problem solving learning model reached 85.04, while the control group that used the scientific learning model only obtained an average score of 74.24. Statistical analysis carried out using the independent sample T test produced a significance value of 0.002, which was below the significance level of 0.05. This finding supports (H1) and rejects (H0), which shows that the application of the problem solving learning paradigm has a significant influence on students' mathematical problem solving abilities